Environmental water efficiency: Maximizing benefits and minimizing costs of environmental water use and management. (9th March 2018) - Horne, Avril C.; O'Donnell, Erin L; Loch, Adam J.; Adamson, David C.; Hart, Barry; Freebairn, John
Abstract : Environmental water management is a relatively new discipline, with concepts, management practice and institutional mechanisms that are still emerging. The efficient and effective use of environmental water to maximize environmental benefits, or environmental water use efficiency, is one such emerging concept. Currently, much of the focus is on allocative efficiency, where the objective is to achieve a better balance between consumptive and environmental water uses in a cost‐effective way. However, this may not provide the most efficient and effective way to manage environmental water in the long term, where managers are seeking productive (or operational) efficiency . Here, the objective is to maximize environmental outcomes relative to the cost of managing the available resource. This paper explores the concept of water use efficiency in the context of environmental water. This article is categorized under: Engineering Water > Planning Water Human Water > Value of Water Abstract : Environmental water use efficiency, highlighting the link between allocative efficiency and productive efficiency. How much water the environment needs depend on how it can be used, and how water is allocated determines how it can be used.